“[L]ike a shoal of fish moving within a net”: 'King Lear' and McGahern’s Family in 'Amongst Women' - Nicholas Taylor-Collins (John McGahern: Critical Essays, 2014)
Parallels between William Shakespeare's 'King Lear' and John McGahern's 'Amongst Women' initiate this chapter. However, while the distinctive presence of women around an ageing and burdened father (Lear and Moran, respectively) join these two narratives, they are also linked by the outsider, base figures of Edmund and Edgar (in 'Lear') and Luke (in 'Amongst Women'). It is the acknowledged abjectness of these brotherly figures who circumscribes and authorises the father's power. Like the classic sovereign in Giorgio Agamben's theories, Lear and Moran derive their power by legislating on the exception, whose presence precedes and creates the possibility of a nuclear family in the first place.